Henri IV dévoilé. Le corps dé-voué du souverain ou la royauté sans sacrifice - Yann Lignereux (Chrétiens et Sociétés, 2013)
Absolutism is not only in the texts and discourses ; we can recognize it in some very bombastic and turgid « places » and acts like ceremonies, great pictures, monuments and somptuous palaces where it appears spectaculary and expressive. But the artistry of power doesn’t work solely with this expansive way. A bronzed statuette made by the french sculptor Barthelemy Prieur can be as demonstrative of absolutist claims of Henri IV’s monarchy as the most famous monuments of the french Absolutism like Versailles, Chambord or equestrian statues. Representing the king’s nudity, this little object shows us the great vocation of the royal power to assume an exceptional autority staging only with the own Prince’s body.